ESSENTIAL ELEMENTS IN A PROGRAM OF INTERNAL AUDIT. - Kohler, E. L. (The Accounting Review, 1953)
Abstract To institute a workable plan for a system of internal audit there must be present those essentials of an underlying structure of management without which a good internal auditor is likely to suffer from continued frustration and the best internal auditor, if he can stay on the job and sweat it out, may find his work singularly ineffective. The first of these organizational essentials is a full-scale recognition of the nature and interdependence of authority, responsibility, and accountability: administrative powers that may be called the three basic operational activators. Second among the essentials is the firing of centers of activity within the various parts of the organizational structure. Third is the empowering of each center with the three operational activators in just the right degree: a quantity and quality of authority designed to provide some freedom of action, the exercise of judgment, no matter how limited, and the development of enthusiasm and pride in work done; a charge of responsibility that will develop, exercise, perhaps even tax supervisory capacities, with substantial curtailment of the need of continuous scrutiny from above; and a scheme of reporting by virtue of which automatic and as far as possible informal accountability is the order of the day.